Improved Composite Gel Electrolyte by Layered Vermiculite for Quasi-Solid-State Dye-Sensitized Solar Cells - Hongcai He; Shuangshuang Ren; Deting Kong; Ning Wang (Advances in Condensed Matter Physics)
A composite quasisolid electrolyte is prepared by adding a layered vermiculite (VMT) into the iodide/triiodide electrolyte including 4-tert-butylpyridine, which obviously improves the photovoltaic properties of quasisolid dye-sensitized solar cells (DSSCs). When adding 6 wt% VMT, the maximum photovoltaic conversion efficiency of 3.89% is obtained, which reaches more than two times greater than that without VMT. This enhancement effect is primarily explained by studying the Nyquist spectra, dark currents, and photovoltaic conversion efficiency.